Challenges of forensic accounting in combating financial corruption in the Algerian environment - benlarbi, abdelmadjid; bouderbala, sara hada (Journal of Research in Finance and Accounting, 2021)
This article aims to shed the light on the challenges facing Forensic accounting in the Algerian environment, and the urgent need to activate and develop this profession in best ways to face the increasing volume of disputes،lawsuits related to fraud, fraud in financial statements and tax declarations in addition to the emergence of New and advanced types of financial crimes resulted from technological development. This article has been formulated based on a main hypothesis that showed the impact of determinants of forensic accounting challenges on combating financial corruption, and four partial hypotheses that focused on the urgent need for forensic accounting services and the most important skills that a forensic accountant should possess to perform and implement his work efficiently and effectivel, All hypotheses were analyzed through the results of statistical analyzes related to answers of a diverse sample of professionals, based on a questionnaire designed for this purpose. Study revealed a set of conclusions, the most important of which is the reject of the main hypothesis and highlighting the critical importance of the determinant of skill in the profession of forensic accounting and it huge impact on the great struggle against all kinds of financial corruption.